Real-time observation of X-ray-induced intramolecular and interatomic electronic decay in CH2I2 - Fukuzawa, Hironobu; Takanashi, Tsukasa; Kukk, Edwin; Motomura, Koji; Wada, Shin-ichi; Nagaya, Kiyonobu; Ito, Yuta; Nishiyama, Toshiyuki; Nicolas, Christophe; Kumagai, Yoshiaki; Iablonskyi, Denys; Mondal, Subhendu; et al. (My University, 2019)
Understanding strong X-ray induced phenomena is important for applications of X-ray free-electron laser imaging. Here, the authors show time-resolved measurements of X-ray free-electron laser induced electronic decay of CH2I2 molecule probed with NIR pulses and identify mechanisms behind different transient states lifetimes.
Keywords: Atomic and molecular interactions with photons; Chemical physics; Free-electron lasers